Persistence properties and blow-up phenomena for a generalized Camassa–Holm equation - Ying Wang; Yunxi Guo (Boundary Value Problems, 2023)
Abstract In this paper, we investigate a generalized Camassa–Holm equation. Firstly, we establish the persistence properties of strong solutions for the equation in weighted spaces L ϕ p = L p ( R , ϕ p d x ) $L^{p}_{φ}=L^{p}(\mathbb{R},φ ^{p}\,dx)$ . Then we present some sufficient conditions of blow-up solutions assuming that the initial data satisfy certain conditions, which are more precise than those in the previous work.